Seminar perlaksanaan Bahasa Malaysia (1983: Universiti Sains Malaysia): Suatu ulasan - Ibrahim, I. (University of Malaya Library, 1983)
At this Seminar, four major themes related to the implementation of Bahasa Malaysia as the medium of instruction of all first year courses in all institutions of higher learning, beginning with the 7983/84 session, were identified and discussed at length. These were: 7. Programmes that have been arranged to teach in Bahasa Malaysia; 2. The proficiency of teaching staff; 3. Terminologies; and 4. The need for text books and other reference books in Bahasa Malaysia.